2019
DOI: 10.1002/alr.22337
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic vs symptomatic septal perforations: a computational fluid dynamics examination

Abstract: Background: A nasal septal perforation (NSP) can lead to frustrating symptoms for some patients while remaining completely asymptomatic for others, without a clear mechanism differentiating them. Methods:We applied individual computed tomography (CT)-based computational fluid dynamics (CFD) to examine the nasal aerodynamics differences between 5 asymptomatic and 15 symptomatic NSP patients. Patients' symptoms were confirmed through interviews, 22-item Sino-Nasal Outcome Test score (asymptomatic, 25 ± 18.8; sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…While dryness, scabbing, epistaxis, and whistling are predominant symptoms in some patients, nasal obstruction is more common in others (1-3). Some patients can remain unaware of a perforation for many years and do not experience nasal obstruction (4). Upon evaluating the data for patients from the current study with the lowest and highest scores on the NOSE scale, the perforations were found to be close in size but were noted to have led to obstructions of varying degrees.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…While dryness, scabbing, epistaxis, and whistling are predominant symptoms in some patients, nasal obstruction is more common in others (1-3). Some patients can remain unaware of a perforation for many years and do not experience nasal obstruction (4). Upon evaluating the data for patients from the current study with the lowest and highest scores on the NOSE scale, the perforations were found to be close in size but were noted to have led to obstructions of varying degrees.…”
Section: Discussionmentioning
confidence: 79%
“…Some studies have also highlighted the importance of considering localization and size together. In a study where the symptoms of patients with NSP were evaluated with the Sino-Nasal Outcome Test-22 (SNOT-22), perforation sizes were found to be larger in asymptomatic patients than in symptomatic patients at a level that was not statistically significant (4). In another study where the sizes of NSPs were measured radiologically, the SNOT-22 values did not correlate with the sizes and positions of the NSPs (17).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Li et al showed that the wall sheer stress (WSS) at this specific region of the perforation was closely correlated with patient symptoms, independent from location or size of the perforation. 34 The perfoplasty technique specifically modifies this posterior edge of the perforation which in turn leads to improved laminar flow through and past the perforation. Paradoxically, enlarging a small perforation in this fashion can actually lead to improved nasal breathing for the patient.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Numerous studies have explored approaches of measuring nasal airflow parameters by in-vitro experiments (11)(12)(13)(14). Gradually, compared with in-vitro replica experiment, researches trend to using computational fluid dynamics(CFD) method since its provides more accurate and detailed prospect of presenting complex and variable airflow patterns (15)(16)(17)(18). Compared with invitro studies, numerical simulation by computational fluid dynamics(CFD) method present significant advantages of providing rich flow patterns and inhalable particles transport.…”
Section: Introductionmentioning
confidence: 99%